Predicted Bacterial Interactions Affect in Vivo Microbial Colonization Dynamics in Nematostella - Domin, Hanna; Zurita-Gutiérrez, Yazmín H.; Scotti, Marco; Buttlar, Jann; Hentschel Humeida, Ute; Fraune, Sebastian (Frontiers in Microbiology, 2018)
The maintenance and resilience of host-associated microbiota during development is a fundamental process influencing the fitness of many organisms. Several host properties were identified as influencing factors on bacterial colonization, including the innate immune system, mucus composition and diet. In contrast, the importance of bacteria-bacteria interactions on host colonization is less understood. Here, we use bacterial abundance data of the marine model organism Nematostella vectensis to reconstruct potential bacteria-bacteria interactions through co-occurrence networks. The analysis indicates that bacteria-bacteria interactions are dynamic during host colonization and change according to the host’s developmental stage. To assess the predictive power of inferred interactions, we tested bacterial isolates with predicted cooperative or competitive behavior for their ability to influence bacterial recolonization dynamics. Within three days of recolonization all tested bacterial isolates affected bacterial community structure, while only competitive bacteria increased bacterial diversity. Already one week after recolonization almost no differences in bacterial community structure could be observed between control and treatments. These results show that predicted competitive bacteria can influence community structure for a short period of time, verifying the in silico predictions. However, within one week, the effects of the bacterial isolates are neutralized, indicating a high degree of resilience of the bacterial community.